Penetração de cloretos em concretos compostos com cinza de lodo de estação de tratamento de água em diferentes teores de adição - Coletto, Tatiani (2017)
The increasing population growth has been responsible for the increasing demand for drinking water and, therefore, an increase in the amount of waste generated in Water Treatment Stations. In the vast majority of municipalities, these wastes, called ETA sludge, are inadequately disposed of in rivers and constitute an environmental problem. Due to this, and the requirements for sustainable construction, the number of researches that seek to substitute part of the cement for agroindustrial by-products is growing, since they enable the reduction in the emission of greenhouse gases, originating from the manufacturing process of this, besides providing economic and technical advantages, guaranteeing greater durability to the structures. However, few published works report the behavior of composite concrete with this mineral addition subject to attack by chlorides. In this work the behavior of the composite concrete with ETA sludge ash (CLETA) was investigated in substitution contents of 5% to 30% Portalnd cement denominated 5L, 10L, 15L, 20L, 25L and 30L, as well as composite ternary mixtures with 5% and 10% of blast furnace slag and 15% of CLETA, denominated 5EAF and 10EAF and a quaternary mixture with 15% of CLETA, 5% of EAF and 5% of husk ash, denominated 5CCA in front of the attack by chlorides. The evaluation was done according to the test method of ASTM C 1202 (rapid chlorine penetration test) at 28 and 91 days in specimens of dimensions 100x51mm and by the silver nitrate sputtering chlorides penetration test (EPCANP ) that allows the determination of the diffusion coefficient of chlorides (K). This test was carried out on test specimens of dimensions 100x100x285mm, immersed in a saline solution at the rate of 31.94g for each liter of distilled water, and assayed at the ages of 7, 14, 28, 56 and 91 days, determining the coefficient of diffusion. In both tests, the specimens were submitted to wet curing for 3 and 7 days and three water / binder ratios were used, 0.35, 50 and 0.65. The results were compared with those obtained in a reference mixture consisting of 100% Portland high initial strength cement. From the results obtained, for both the tests adopted, there is an increase in the resistance to the penetration of chlorides with the increase in the curing time and the substitution content of the Portland cement (ARI) by the sludge ash from the water treatment plant (CLETA ). The ternary and quaternary mixtures presented better performance than the reference mixture, however, lower than that composed with 30% of CLETA.